Ninel Vasylivna Deduh - “Orthopaedics, Traumatology; Prosthetics”, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is dedicated to a talented researcher whose name is widely known in the world, an outstanding morphologist in the field of musculoskeletal system, Doctor of Biological Sciences, Professor Dedukh N.V.